Religion as we know it: an origin story - Vasconcellos, Danilo Souza Mendes de (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2020)
Resenha MILES, Jack. Religion as we know it. An Origin Story. Nova Iorque: Norton, 2020. 152p. ISBN: 978-1-324-00278-9.